The WTO and environmental sustainability: is there a conflict?. (1st January 2003) - Belcher, Ken; Hobbs, Anna L.; Kerr, William A.
In recent years, the World Trade Organisation (WTO) has been the focus for many complaints involving environmentally-based trade disputes between countries. As a result, there has been increasing pressure for the WTO to explicitly address environmental issues in its governance of barriers to international trade. In this paper, we examine the main areas of conflict between WTO provisions and sustainable management of the environment. In particular, we highlight potential impacts, both negative and positive, of trade liberalisation and WTO principles for environmental sustainability. Finally, we discuss measures for resolving the trade-environment controversy.